Exploring the Relationship between Sociocultural Identity and Lexical Richness: Insight from High School Students’ Writing - Syafri, Mohamad; Akhiryani, Atna; Mardiah, Anna; Andini, Melly (Journal of Foreign Language Teaching and Learning, 2025)
Background: Many variables, including culture and social conditions, bind language. The study of cultural aspects and language learning still has many gaps, such as exploring writing skills. Writing is considered a productive language skill that correlates with how students express and understand their circumstances and environments. Objective: Therefore, this research explores sociocultural identity with Lexical Richness in text writing. Methods: This research was conducted using a quantitative method. The research design is correlational analysis. The research participants were 86 eleventh grade students selected by purposive random sampling. The results showed that the significance value was 0.575, so it was concluded that there was no significant relationship between sociocultural identity and lexical richness in writing. Findings: In addition, the research also found a high gap among students in expressing ideas with diverse words, where the range between the most and least varied text was 47% and the average 56.9%. It is hypothesized that the students' basic ability to use English will be a crucial indicator that influences competence before other external factors, such as their cultural background interference. In addition, this research can serve as a basis for future studies, especially considering that external factors in learning can play a role depending on prerequisite conditions. Conclusion: For teachers and educators, this research could give insight into a more applicable way to develop vocabulary and writing.